Cinematherapy Counseling sebagai Pendekatan Sosialisasi Pentingnya Pendidikan di SD Negeri 05 Semingkir - Raniasati, Rifani; Ragil, Ayu Wahyuning; Milah, Vina Indana; Nugroho, Bagus Purwo; Astiti, Niken; Priyanto, Aris (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research is motivated by problems in education where children in Semingkir Village are not provided with proper education facilities, resulting in dropping out of school and having to earn a living after graduating from school. This activity is carried out in the form of observation and delivery of materials targeting students of SD Negeri 05 Semingkir Village. Coordination activities are carried out through socialization of the importance of education to provide a view of awareness of the importance of education to students. Socialization of education is carried out to support the program of the system. As well as education and counseling through cinematherapy to project and implement moral messages.